Hydroprocessing of rubber seed oil over Ni-Mo/γ-Al2O3 for the green diesel production - Ameen, M. (Italian Association of Chemical Engineering - AIDIC, 2017)
Hydrodeoxygenation is most considered route for up-gradation of biodiesel and triglycerides towards direct conversion into diesel range hydrocarbon (green diesel). Heterogeneous (Ni-Mo/γ-Al2O3 catalysts) catalysis offers more promising routes for transformation of biomass into value added bio-chemicals more likely selective hydrocarbons in a resourceful approach. In this study, the Ni-Mo/γ-Al2O3 type catalysts were investigated for the hydrodeoxygenation of rubber seed oil for the diesel range hydrocarbons (n-C15-n-C18). Monometallic solid acid catalysts (Ni/γ-Al2O3) and bimetallic (Ni-Mo/γ-Al2O3) catalysts were tested for HDO reaction at 340 oC, 21 bar, H2/oil ratio 150 Nm3/m3 using 5 g, WHSV = 10 h1 for 5 h time on stream in tubular fixed bed reactor (pilot scale). Among the sonochemically synthesized catalysts, 3 wt. Ni/γ-Al2O3 showed the higher catalytic activity up to 15.4 wt. and bimetallic Ni-Mo/γ-Al2O3 was perceived to be more active with 15.35 wt. diesel range (C15-C18) hydrocarbons from rubber seed oil. The selectivity for n-C15-n-C18 hydrocarbons were determined as C15 (7.14 ), C16 (7.16 ), C17 (0.42) and C18 (0.78) among the liquid alkanes. The product distribution revealed that the reaction proceeded mainly with decarboxylation (DCO2) and decarbonylation (DCO) with high C15/C16 ratio. The results from hydrodeoxygenation of rubber seed oil showed an innovative reaction path for the production of diesel range hydrocarbons. The monometallic 3 wt. Ni/Al2O3 and 15 wt. Ni/Al2O3 synthesized via conventional method showed lower triglycerides conversion with 63 wt. and 70 wt. respectively. All the sonochemically synthesized catalysts revealed complete conversion of triglycerides (99 wt.) into other paraffin, olefins and oxygenates and showed better activity even at low operational parameters for hydrodeoxygenation of triglycerides present in rubber seed oil. Copyright © 2017, AIDIC Servizi S.r.l.